Wpływ regulacji prawnych Unii Europejskiej na polskie specjalne strefy ekonomiczne - Gibuła, Ryszard (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The author presents in the article the complicated matter connected with the existence of special economic areas in Poland and the regulations of common law concerning this domain. The article contains the definition of such areas, presentation of European public aid policy and the description of the Polish regulations evolution. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 142-161